"I'm Not a Vet!" Marginalisation and Practices of Resistance to Ageing by Women Hockey Players. Issue 1 (2nd January 2019) - Forsdike, Kirsty; Sawyer, Anne-Maree; Marjoribanks, Timothy
ABSTRACT: Participation in team sports constitutes both a site for perpetuating discriminatory cultural perceptions of ageing women as well as a means of resisting and challenging such perceptions. Using Markula's framework of Foucauldian feminism, we examine the marginalisation of women who play hockey in Australia and their acts of resistance against discriminatory processes related to ageing. This analysis draws on an ethnographic study of an Australian women's field hockey club. Fifteen women took part in two one-on-one in-depth interviews focused on their experiences of mental health and emotional well-being in relation to playing hockey. Although participating in a team sport offers a means of resisting negative stereotypes of ageing women, the quasi-professionalisation that occurred at this particular club across the data collection period constrained these women's acts of resistance. These findings illuminate the impact of a club's structure and culture on women's experiences of social inclusion in the context of Australian team sport.